Enhancing Smart Cities’ Resilience Through Competency Assessment and Open Data Utilization - Isabel Ramos; Victor Barros; Angelika Kokkinaki; Chrysostomi Maria Kyrillou; Alkis Thrassou; Katharina Ebner; Christian Anschütz; Panos Fitsilis; Paraskevi Tsoutsa; Theodor Panagiotakopoulos; Achilles Kameas (Applied Sciences)
The increasing frequency of natural catastrophes and other disasters has underscored the importance of resilience as a core competence for smart cities so that they efficiently manage unforeseen crises. The increasing recognition of resilience in the context of smart cities leads to examining the role and context for the role of the “Smart City Resilience Officer” (SCRO). This article addresses this research gap by exploring the significance of resilience in smart cities and introduces a self-assessment model for evaluating the skills of professionals tasked with its management. Additionally, it emphasizes the role of open data in enhancing smart city resilience, whose utilization offers significant benefits, such as increased transparency, improved collaboration among stakeholders, and the ability to harness data-driven insights for more effective resilience strategies. This article identifies and defines the requisite competencies for SCROs to differentiate them from other city managers and develops a self-assessment tool featuring 20 key competencies. This tool was evaluated by smart city stakeholders in the consortium countries of the OpenDCO Erasmus+ project using a competencies assessment methodology. This study highlights the role of resilience policies in Europe and in launching large-scale training programs that develop competencies and facilitate the sharing of experiences and best practices. The findings underscore the potential of competency assessment and open data utilization in advancing the resilience of smart cities.